ANALISIS STRATEGI KEPALA SEKOLAH DALAM MENGEMBANGKAN MUTU PENDIDIKAN SEKOLAH DASAR - Nurdiana, Nurdiana; Nurdjan, Sukirman; Saleh, Mahadin (Kelola: Journal of Islamic Education Management, 2023)
This researach discusses the Study of the Principal's Leadership Strategy in Improving the Quality of Education at SDN Telluwanua District, Palopo City. the problem in this study is the lack of management of school principals in improving the quality of education. This study aims to determine the leadership management of school principals in the delivery of education and the impact of educational outcomes at SDN Telluwanua District, Palopo City. The type and research approach used is descriptive quantitative. The source of the data used is primary data obtained from interview instruments with respondents, namely the principal, educators and teaching staff at SDN 18 Maroangin, SDN 52 Salutete and SDN 51 Sumarambu. The results of this study showed that 1. The strategy for improving the quality of education at SDN Telluwanua District, Palopo City began with the commitment of the school principal to improve the quality of education by planning a strategy, followed by improving the school's organizational structure, increasing the competence of educators and education staff, increasing student achievement, fulfillment of facilities infrastructure, building cooperative networks, creating independent school programs and evaluating educators, education staff and school programs. 2. The impact of educational outcomes at SDN schools in Telluwanua District, Palopo City, is that teacher competence has increased, graduation rates and graduate absorption have increased, school performance and school image have increased and facilities and infrastructure have begun to be fulfilled. The implication of this research is that by referring to the results of this study, it is better if the leadership management of school principals in improving the quality of education is increased again from before so that the goals of education in schools can be achieved effectively and efficiently.